How are Interactions Taken into Account in Studies on Conventional and Complementary Therapies for Breast Cancer Patients with Menopausal Complaints? - Hübner, J.; Münstedt, K.; Mücke, R.; Micke, O. (Geburtshilfe und Frauenheilkunde, 2012)
Introduction: Postmenopausal symptoms in breast cancer patients undergoing antihormone treatment lead to high drop-out rates from the therapy. From the therapeutic point of view, methods of both conventional and complementary medicine are concerned. Interactions are being discussed in cases of natural substances. However, they are also relevant for conventional medical substances. The aim of this analysis is to answer the question as to what extent potential interactions are taken into account in clinical studies and reviews on supportive therapies. Materials and Methods: Clinical studies and reviews were identified by means of a systematic search and analysed with regard to the consideration of potential interactions. Results: Altogether 46 clinical studies and one Cochrane review were found. Among the 35 studies on conventional drug therapies, 5 (14 %) took possible interactions into account. Among the 17 studies on complementary medicine, there were 2 (11.7 %) such publications. The Cochrane review did not mention interactions. Discussion: For future studies in which interactions cannot be excluded, a strategy to control for their clinically relevant consequences should be developed. The present authors suggest that the use of survival and recurrence data as secondary endpoints, also for studies on purely supportive therapies, is a reasonable approach. The resulting considerations for study routines are listed thematically.
Keywords: breast cancer; antihormone therapy; hormone withdrawal signs; complementary medicine; interactions